Respuesta :
Answer: [tex]7m^5-3m^3-3[/tex]
Step-by-step explanation:
You can observe that you need to subtract the polynomial [tex](6m^5 + 3 - m^3 -4m)[/tex] and the polynomial [tex](-m^5 + 2m^3- 4m + 6)[/tex].
It is important the remember the multiplication of signs:
[tex](+)(+)=+\\(-)(-)=+\\(+)(-)=-[/tex]
Then, the first step is to distribute the negative sign:
[tex](6m^5 + 3 - m^3 -4m)-(-m^5 + 2m^3- 4m + 6)=\\=6m^5 + 3 - m^3 -4m+m^5-2m^3+ 4m- 6[/tex]
And finally you must add the like terms. Then:
[tex]=7m^5-3m^3-3[/tex]